1997
DOI: 10.1111/j.1365-2389.1997.tb00555.x
|View full text |Cite
|
Sign up to set email alerts
|

Measurement of volumetric water content by TDR in saline soils

Abstract: Time-domain reflectometry (TDR) evaluates the bulk dielectric constant, K , of the soil by measuring the travel time of an electromagnetic pulse through a sensor, and through it estimates the volumetric water content. We show that for saline soils the effects of conductivity and frequency on the travel time cannot be neglected and that, as a result, TDR systematically overestimates the water content in saline soils. Simultaneously the bulk electrical conductivity of soils can be estimated by TDR. The equivalen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
55
0
1

Year Published

2000
2000
2015
2015

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 86 publications
(58 citation statements)
references
References 19 publications
2
55
0
1
Order By: Relevance
“…The degree of humification was similar to that of the O co horizon (Table 2), but the organic matter may come from other plant species and have different electrical characteristics. In this horizon, the salinity was too low (Table 2) to influence the Ka value (Wyseure et al 1997) as in the two other horizons. The particulate structure, the type of organic matter and the characteristics of the porous system of this horizon seem to be the principal factors affecting the difference between the O hp horizon and the O f and O co horizons.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The degree of humification was similar to that of the O co horizon (Table 2), but the organic matter may come from other plant species and have different electrical characteristics. In this horizon, the salinity was too low (Table 2) to influence the Ka value (Wyseure et al 1997) as in the two other horizons. The particulate structure, the type of organic matter and the characteristics of the porous system of this horizon seem to be the principal factors affecting the difference between the O hp horizon and the O f and O co horizons.…”
Section: Resultsmentioning
confidence: 99%
“…For some unclear reasons, the organic matter content did not seem to affect the variability as much as the organic matter characteristics (particle size and humification level) ( Table 2). The salinity of these two horizons was different (Table 2), but too small to influence Ka values (Wyseure et al 1997). The use of a single relationship for these two horizons overestimated u (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…The differences between the observed salinity ranges for which a universal calibration could be applied in this study and that reported by Inoue et al (2008) might be attributed to the differences in soil texture and the instrument used. Wyseure et al (1997) found the TDR measurement errors exceeded acceptable levels in different saline soils when EC of the saturated paste extract exceeded 8 to 10 dS m -1 , while Sun et al (2000) stated a 10 dS m -1 limit in saline fine sands. In a study that examined TDR probes in sands over 0 to 40 dS m -1 pore water EC range, Hook et al (2004) reported that the effect of soil salinity on VWC errors was not apparent until the EC reached 25 dS m -1 .…”
Section: The Acclima Digital Tdt Sensormentioning
confidence: 99%
“…Evett et al (2005) found that TDR measurements may be affected by soil salinity, soil temperature, clay type and clay content. The TDR technique may overestimate soil-water content in saline soils because the apparent dielectric constant also depends on the electrical conductivity of the soil (Wyseure et al, 1997). For example, Wyseure et al (1997) used a dielectric-based technique to estimate the electrical conductivity.…”
Section: Introductionmentioning
confidence: 99%
“…The TDR technique may overestimate soil-water content in saline soils because the apparent dielectric constant also depends on the electrical conductivity of the soil (Wyseure et al, 1997). For example, Wyseure et al (1997) used a dielectric-based technique to estimate the electrical conductivity. Miyamoto and Maruyama (2004) found that by coating the TDR rods, more accurate measurements in a heavily fertilised paddy field was possible.…”
Section: Introductionmentioning
confidence: 99%